Simple and Effective Curriculum Pointer-Generator Networks for Reading Comprehension over Long Narratives - Tay, Yi; Wang, Shuohang; Tuan, Luu Anh; Fu, Jie; Phan, Minh C.; Yuan, Xingdi; Rao, Jinfeng; Hui, Siu Cheung; Zhang, Aston (ACL 2019, 2019)
This paper tackles the problem of reading comprehension over long narratives where documents easily span over thousands of tokens. We propose a curriculum learning (CL) based Pointer-Generator framework for reading/sampling over large documents, enabling diverse training of the neural model based on the notion of alternating contextual difficulty. This can be interpreted as a form of domain randomization and/or generative pretraining during training. To this end, the usage of the Pointer-Generator softens the requirement of having the answer within the context, enabling us to construct diverse training samples for learning. Additionally, we propose a new Introspective Alignment Layer (IAL), which reasons over decomposed alignments using block-based self-attention. We evaluate our proposed method on the NarrativeQA reading comprehension benchmark, achieving state-of-the-art performance, improving existing baselines by 51% relative improvement on BLEU-4 and 17% relative improvement on Rouge-L. Extensive ablations confirm the effectiveness of our proposed IAL and CL components.
ArXiv